Detailed cost of robotic-assisted surgery in the Australian public health sector: from implementation to a multi-specialty caseload - Kate McBride; Daniel Steffens; Christina Stanislaus; Michael Solomon; Teresa Anderson; Ruban Thanigasalam; Scott Leslie; Paul G. Bannon (BMC, 2021)
Abstract Background A barrier to the uptake of robotic-assisted surgery (RAS) continues to be the perceived high costs. A lack of detailed costing information has made it difficult for public hospitals in particular to determine whether use of the technology is justified. This study aims to provide a detailed description of the patient episode costs and the contribution of RAS specific costs for multiple specialties in the public sector. Methods A retrospective descriptive costing review of all RAS cases undertaken at a large public tertiary referral hospital in Sydney, Australia from August 2016 to December 2018 was completed. This included RAS cases within benign gynaecology, cardiothoracic, colorectal and urology, with the total costs described utilizing various inpatient costing data, and RAS specific implementation, maintenance and consumable costs. Results Of 211 RAS patients, substantial variation was found between specialties with the overall median cost per patient being $19,269 (Interquartile range (IQR): $15,445 to $32,199). The RAS specific costs were $8828 (46%) made up of fixed costs including $4691 (24%) implementation and $2290 (12%) maintenance, both of which are volume dependent; and $1848 (10%) RAS consumable costs. This was in the context of 37% robotic theatre utilisation. Conclusions There is considerable variation across surgical specialties for the cost of RAS. It is important to highlight the different cost components and drivers associated with a RAS program including its dependence on volume and how it fits within funding systems in the public sector.